Pushing it to the Limit: Adaptation with Dynamically Switching Gain Control. (8th November 2006) - Keil Keil, Matthias S. Matthias S.; Vitrià Vitrià, Jordi Jordi
Abstract : With this paper we propose a model to simulate the functional aspects of light adaptation in retinal photoreceptors. Our model, however, does not link specific stages to the detailed molecular processes which are thought to mediate adaptation in real photoreceptors. We rather model the photoreceptor as a self-adjusting integration device, which adds up properly amplified luminance signals. The integration process and the amplification obey a switching behavior that acts to shut down locally the integration process in dependence on the internal state of the receptor. The mathematical structure of our model is quite simple, and its computational complexity is quite low. We present results of computer simulations which demonstrate that our model adapts properly to at least four orders of input magnitude.